The influence of pneumococcal positivity on clinical outcomes among patients hospitalized with COVID-19: A retrospective cohort study - Chang-Seok Yoon; Ha-Young Park; Hwa-Kyung Park; Jae-Kyeong Lee; Bo-Gun Kho; Hong-Joon Shin; Yong-Soo Kwon; Yu-Il Kim; Sung-Chul Lim; Tae-Ok Kim (PLoS ONE, 2025)
Background Bacterial co-infection has been associated with adverse outcomes in patients with COVID-19. Streptococcus pneumoniae is a common cause of community-acquired pneumonia and may contribute to poor clinical outcomes when co-detected in COVID-19 patients. This study aimed to investigate the clinical significance of pneumococcal positivity in hospitalized patients with COVID-19. Methods We conducted a retrospective analysis of adult patients hospitalized with COVID-19 at two tertiary care centers. Pneumococcal positivity was defined by either a positive urinary antigen test or multiplex real-time polymerase chain reaction. Disease severity of COVID-19 pneumonia was assessed using the pneumonia severity index and CURB-65 scoring systems. Propensity score matching and multivariable logistic regression were used to adjust for confounders and identify independent risk factors for mortality. Results Among 280 patients, 65 pneumococcus-positive patients were matched with 65 pneumococcus-negative patients after propensity score matching. In the overall matched cohort, pneumococcal positivity was not significantly associated with in-hospital mortality. However, in patients with severe disease (n = 156), defined as pneumonia severity index >130 or CURB-65 ≥ 3, mortality was significantly higher in pneumococcus-positive patients (n = 39) than in pneumococcus-negative patients (53.8% vs. 29.1%, p = 0.009). In the multivariable analysis of this subgroup, pneumococcal positivity (odds ratio, 4.050; 95% confidence interval, 1.285–12.765; p = 0.017) and high-flow oxygen therapy (odds ratio, 6.510; 95% confidence interval, 1.847–22.944; p = 0.004) were independently associated with mortality. Conclusion Detection of S. pneumoniae by urinary antigen test or multiplex polymerase chain reaction was associated with increased mortality in patients hospitalized with severe COVID-19.